A review of influence of slow release fertilizer on growth of rubber (Hevea) seedling / Safiah Musa - Musa, Safiah (Faculty of Plantation and Agrotechnology, 2017)
Rubber, Hevea brasiliensis is a valuable crop of some countries in Asia, it is has several usage of rubber that has been founded from time to time such as latex production, and now is timber. Usually rubber woods have been used in furniture making. Malaysia rubber sector has reach export value about RM 3115 million in years 1999 it is about 2% of total Malaysia export industries. Effective fertilizer application is important in producing high yield of rubber latex and high quality of timber wood. Nutrients are important and necessary for plant growth and produce high yield. Nitrogenous fertilizer is very important to rubber growth especially in growing stage. This review to determine the efficiency of slow-released fertilizer on rubber growth, this is also to compare the advantages between of slow and quick-released fertilizer. The other objective of this review is to determine the important of nutrient for rubber growth and the last is to know how the slow released fertilizer work in the soil. Nutrient use efficiency (NUE) is the amount of nutrient uptake by plants. The rate of N minerals need by rubber is about 50-70% during the first year of growth. Slow fertilizer is able to release about 80% of N over 40 days. Low burn of scorching potential to seedling especially of leaf is one of the advantage of slow-release fertilizer, and fast release of nutrient is the advantage of quick fertilizer which is plant root are able to uptake the nutrient in short time. Nitrogen is important for rubber growth and it is need greater amount rather than other nutrient, nitrogen absorption is important support for plant chlorophyll and proteins forming. Urea formaldehyde (UF) are the most suitable for rubber plantation in Malaysia, it is contain 38% of nitrogen. However, optimum fertilizer level for rubber growth and development is 150%, while 200% will considered as excessive for plant.